The Impact of Pre-Trade Transparency on Market Quality and Retail Participation in the Pre-Opening Session of the Indonesia Stock Exchange - Famy Kurnia Putri; Rofikoh Rokhim (Green Publisher Indonesia, 2025)
This paper examines the impact of enhanced pre-trade transparency on market quality during the pre-opening session of the Indonesia Stock Exchange (IDX) in the pre and post period of enhanced pre-trade transparency starting from March, 25th 2024. Pre-trade transparency refers to the disclosure of order prices and volumes prior to transaction execution, a crucial factor in market efficiency and price discovery. Utilizing empirical data from LQ45 index constituent over the period of October 2023 to September 2024, this paper examines the effects of enhanced pre-trade transparency on market quality, such as bid-ask spread, market depth, and overnight volatility. Based on multiple linear regression analysis, the findings reveal that increased pre-trade transparency significantly narrows the bid-ask spread, enhances market depth, and boosts retail investor participation. However, it also contributes to an increase in overnight volatility.